2006
DOI: 10.1186/1472-6963-6-66
|View full text |Cite
|
Sign up to set email alerts
|

Development and preliminary validation of a Greek-language outpatient satisfaction questionnaire with principal components and multi-trait analyses

Abstract: Background: In the recent years there is a growing interest in Greece concerning the measurement of the satisfaction of patients who are visiting the outpatient clinics of National Health System (NHS) general acute hospitals. The aim of this study is therefore to develop a patient satisfaction questionnaire and provide its preliminary validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
2
22
0
1
Order By: Relevance
“…While longer waits on waiting rooms have a strongly negative correlation with overall satisfaction [ 38 ], longer duration of the consultation time has been associated with higher levels of overall satisfaction in ambulatory practice [ 39 , 40 ]. The physical environment of hospital outpatient services has also been reported to influence satisfaction [ 41 , 42 ], with 94–96 % of our respondents scoring it as ’better’/’much better’ than expected.…”
Section: Discussionmentioning
confidence: 84%
“…While longer waits on waiting rooms have a strongly negative correlation with overall satisfaction [ 38 ], longer duration of the consultation time has been associated with higher levels of overall satisfaction in ambulatory practice [ 39 , 40 ]. The physical environment of hospital outpatient services has also been reported to influence satisfaction [ 41 , 42 ], with 94–96 % of our respondents scoring it as ’better’/’much better’ than expected.…”
Section: Discussionmentioning
confidence: 84%
“…These results concurred with those presented in other studies. [ 32 , 34 , 35 ] Results of a logistic regression identified that age, occupation, education background, and type of medical insurance of the patients could be determinants of their overall satisfaction. Several studies [ 26 , 32 , 34 ] concluded that younger patients had a lower satisfaction rate.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 The first part of the questionnaire included five items, on patient demographic variables such age, occupation, marital status, house income and education level. The second part included 28 items about service quality of the obstetrics and gynaecology clinic services: appointment system (seven items), clinic facility (four items), staff's professionalism (four items), the communication (three items), your visit with providers (seven items) and patient's overall satisfaction (three items).…”
Section: Methodsmentioning
confidence: 99%